Low Global Physical Activity Despite Two Decades of Policy Progress - Ramírez Varela, Andrea; Bauman, Adrian; Woods, Catherine B; Shawar, Yusra Ribhi; Hallal, Pedro C; Salvo, Deborah; Siefken, Katja; Wendel-Vos, Wanda; Miranda, J Jaime; Mejía-Grueso, Juliana; Sallis, James F; Hinckson, Erica; et al. (Springer Science and Business Media LLC, 2026)
Global physical inactivity has remained high and unchanged for the past two decades. We assessed global political priority for physical activity. An analysis of national policy documents from 200 countries revealed notable progress in policy adoption since 2004, but we found limited evidence of implementation. A qualitative case study design, including insights from 46 key informants, confirmed low political priority. Four key challenges emerged: (1) domination of health-centric approaches; (2) limited recognition of benefits beyond non-communicable disease prevention; (3) interest across sectors but lack of clarity defining physical activity policy and of leadership; and (4) limited multisectoral partnerships. Proposed solutions include: (1) building consensus on physical activity policy with consideration of context; (2) acknowledging the scope of benefits; (3) clarifying multisectoral leadership and responsibilities; and (4) increasing partnerships beyond obvious proponents. Prioritizing physical activity policy is essential for improving human, societal and planetary health.
Keywords: 4206 Public Health; 42 Health Sciences; Physical Activity; Prevention; 8.3 Policy, ethics, and research governance; 3 Good Health and Well Being